African musical instruments in Kenya - Hyslop, Graham H. (International Library of African Music, 1958)
There are many African musical instruments scattered throughout Kenya. In some cases it appears that there will be nobody to carry on this tradition when the present exponent dies. This means that in a short time, some of the traditional instruments of this country will have been lost without trace. Because of this danger, traditional instrumentalists were invited to attend a Course at Jeanes School, the Colony’s main centre for Adult Education, in September, 1958, in order that a careful study of these instruments might be made.
Keywords: Stringed instruments; Musical instruments; Ethnomusicology; Percussion instruments; Kenya; African Music